PENGUNAAN METODE HIRARC DALAM MENGANALISIS RISIKO K3 PADA BAGIAN PENGEMASAN - Bintang Ardiyansyah; Ardhy Lazuardy; Arief Nurdini (Jurnal Teknik dan Science, 2024)
PT Mandom Indonesia Tbk. is a company that manufactures cosmetic products. In the process of packing, operators are directly related to work and have a risk of work accidents. PT Mandom Indonesia's work accident data in the last 3 years (2020 - 2022) shows that there are still work accidents in the packaging section, in 2020 there were 6 cases of work accidents, in 2021 there were 4 cases of work accidents, and in 2022 there were 3 cases of work accidents. This proves the need to implement occupational safety and health to reduce work accidents. This paper aims to identify potential hazards and risks, assess the level of risk that has been identified, and control risks that can potentially cause work accidents in the packaging section. HIRARC is a method of identifying potential hazards found in each type of work. Hazard identification is carried out in the packaging section. The packaging section has 10 work activities with 28 potential hazards. The risk assessment results carried out in the packaging section are 28 potential hazards and potential risks with 8 high risk, 11 medium risk, and 9 low risk. Risk control is carried out on activities with high and medium risks. Of 10 work activities, 9 still have 8 high risk and 11 medium risk. After controlling, the final assessment results in the packing section show a decrease, namely to 8 medium risk and 11 low risk. The controls carried out are engineering, administration, and using PPE.